The Impact of Brand Equity on Brand Preference and Purchase Intention in Indonesia’s Bicycle Industry: A Case Study of Polygon - Felly Liliyana Soenyoto (iBuss Management, 2015)
In the midst of stiff competition of local and foreign brands in Indonesia’s bicycle industry, understanding the role of a brand in  influencing consumer’s brand preference and purchase intention is becoming more important as more choices are available for consumers. Thus, taking the case study of Polygon, this research aims to investigate the impact of brand equity on consumer’s brand preference and purchase intention as well as the possibility of brand preference as the mediator between brand equity and purchase intention.  Through an online platform of questionnaire, 121 respondents were gathered from both Polygon existing consumers and other bicycle consumers whom have not had Polygon bicycle. The data gathered was analyzed using the linear regression and sobel test. The result shows that brand equity has significant impact on brand preference and purchase intention. Brand preference is also proven to significantly impact consumer’s purchase intention. Finally, brand preference is confirmed to mediates the impact of brand equity on purchase intention. Thus, bicycle companies, especially the PT Insera Sena as the company of Polygon brand, should focus on improving their brand equity to increase consumer’s brand preference and purchase intention of their brand.Keywords:  Brand Equity, Brand Preference, Purchase Intention, Consumer  Behavior, Brand Management.